P201 How can sexual history taking for sexually transmitted infection partner notification be improved?. (8th June 2017) - Vojt, Gabriele; Pothoulaki, Maria; Estcourt, Claudia; Flowers, Paul; Mapp, Fiona; Woode-Owusu, Melvina; Mercer, Cath; Saunders, John; Cassell, Jackie; Nandwani, Rak; Symonds, Merle
Abstract : Introduction: National guidelines, standards and policies help health care professionals to elicit information during sexual history taking as part of partner notification (PN) for sexually transmitted infections (STI). Accurate information about sexual partners and sexual behaviours is vital to prevent onward transmission. This study focuses on patients' experiences on how sexual history questions for the purpose of PN could be improved. Methods: We conducted 12 focus groups with members of the public and patients at sexual health clinics in Glasgow and London. All patient participants had been diagnosed with a (non-HIV) STI in the past six months. Data were analysed using thematic analysis. Results: Analysis revealed a number of interrelated themes arising from participants' experiences and perceptions. Shared beliefs about sensitivity and reflexivity of questions regarding the frequency, riskiness and contactability of sexual partners influenced the way in which patients experienced and responded in sexual health consultations. Congruence in language and clinician-led consideration of the context of individual sexual behaviour contributed to the extent to which information was shared. Discussion: Sexual history taking for PN is embedded within a complex interaction between clinicians and patients. The need to accurately identify all partners is balanced against acknowledging that questions asked must be sensitive yet unambiguous. This study suggests that establishing congruence in language and investing time to examine contextual factors within the patient's sexual behaviours can lead to active collaboration within a time-efficient window, and enhancing the accuracy of information shared thereby enabling health professionals to offer appropriate options for PN.